Optimalisasi Fungsi Organisasi Persatuan Istri Karyawan Gresik Cipta Sejahtera (PIKGCS) Melalui Penguatan Kepribadian Pengurus dan Anggota - Hidayati, Roziana Ainul (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Mental health disorders are not visible from the outside, but their sudden impact can cause unexpected things that can be detrimental to the organization. The aim of this dedication is to strengthen the mental health of PIKGCS members and administrators so that their personality as mothers/wives of PT employees. GCS becomes stronger and tougher, not easily fragile. With a strong personality, you will be able to optimally support your husband's career while creating family peace. The method used in this activity is counseling/seminars. The result of this service is that in the initial session the participants were given an understanding of what mental health is and the importance of mental health for a mother. Mental disorders do not mean crazy, but mental disorders that are not treated immediately can tend to result in mental disorders (insanity). Indications of mental disorders in them include excessive anxiety, stress, lack of self-confidence and depression. The factors that cause a mother to experience these mental disorders are lack of interaction, having excessive expectations about something, no one to support her, work demands, an uncomfortable environment, poor stress management, and not having time for herself. A mother who experiences mental disorders certainly has an impact on the family. So the important things to pay attention to so that mental disorders don't get worse are staying away from toxic environments, taking time for yourself, asking for support from your family, especially your husband, consuming healthy and halal food, and if necessary, consulting a psychologist and developing self-management skills. The self-management skills referred to include time management, spiritual management, physical management, social environmental management, emotional (psychic) management.